Substrate integrated waveguide‐based simultaneous transmit and receive antenna for full‐duplex wearable devices - Mallat, Nazih Khaddaj; Iqbal, Amjad (International journal of RF and microwave computer-aided engineering, 2022)
In this paper, a low‐size and compact substrate integrated waveguide (SIW)‐based simultaneous transmit and receive antenna is developed for full‐duplex wearable telemetry applications. The antenna operates at 4.9 GHz (Wireless Local Area Network [WLAN]) and 5.8 GHz (Industrial, Scientific and Medical [ISM]) bands with acceptable gains. Keeping a proper gap between the two ports achieves an isolation of better than 29.8 dB. This antenna is kept compact (0.20 λg2, where λg is the wavelength at 4.9 GHz) by additional arc‐shaped slot in each radiator, which adds additional capacitance. The suggested antenna is simulated inside a 52 × 63 × 17 mm3 dummy wearable telemetry device and is worn on the subject's chest. Thanks to SIW technology, it has unidirectional radiation patterns, allowing a minimum beam towards the human body, and thus, offers lower specific absorption rate (SAR) at both frequency bands. The unique advantage is its capacity to receive and transmit the telemetry signals simultaneously. Its low profile, flexibility in the resonant bands, simultaneous transmission and reception, and lower SAR values make this antenna suitable for full‐duplex wearable telemetry devices.